Complications During and After Extraction of Third Molar - Alazzawi, Amena; Ghazi, Mohammed; Jikia, Maia (Caucasus Journal of Health Sciences and Public Health, 2018)
Background: The removal of the third molar is one of the most frequent and common procedures in oral and maxillofacial surgery. Reasons of extraction might be impacted tooth associated with caries, pericoronitis, periodontal defects in the distal surface of second molar, odontogenic cyst and dental crowding. Difficulty of extraction is due to many factors and could happen during and after removal of the third molar, which we are going to represent in this article. Factors influence the incidence of complications: there are many factors and determinants which have an influence on the incidence of complications. Such as age, gender, depth of impaction, degree of difficulty, experience of the surgeon and patient’s medical condition. All of these factors could effect on the successfulness of third molar extraction. Intraoperative complications: during extraction of third molar, some complications could occur even with an expert surgeon. Examples of complications during extraction of third molar could be nerve damage, mandibular fracture, and displacement of third molar, hemorrhage, subcutaneous emphysema and soft tissue injury. Postoperative complications: complications are not only restricted during extraction, but also it can happen after the extraction. An example of postoperative complications would be localized alveolar ostietis, inflection, bleeding, paresthesia, alveolitis, and trismus and hematoma formation. Advices and habits to avoid: successful of the extraction doesn't depend only on the dentist and his ability, but also depends on patient's cooperation with the dentist. Conclusion: studying the complications of third molar extraction would enhance student's knowledge, and prepare her or him to future challenges. And also learning these complications would support the student’s confidence and ability in the future.